Isotopic composition of total gaseous mercury at a high-altitude tropical forest site influenced by air masses from the East Asia continent and the Pacific Ocean. (1st February 2021) - Nguyen, Ly Sy Phu; Sheu, Guey-Rong; Fu, Xuewu; Feng, Xinbin; Lin, Neng-Huei
Abstract: Gaseous elemental mercury (GEM), gaseous oxidized mercury (GOM), particulate-bound mercury (PBM), and the isotopic composition of total gaseous mercury (TGM = GEM + GOM) were measured at the Lulin Atmospheric Background Station (LABS), a mountain background site downwind of the East Asia continent, from February 2015 to January 2016. Mean (±S.D.) concentrations of GEM, GOM, and PBM were 1.54 ± 0.34 ng m −3, 14.0 ± 27.8 pg m −3, and 2.6 ± 3.7 pg m −3, respectively. Concentration-Weighted Trajectory (CWT) analysis indicated that East and coastal China were the main source regions of elevated GEM observed at LABS. Weekly integrated TGM showed significant variations in δ 202 HgTGM (−0.42 to 0.41‰) and Δ 199 HgTGM (−0.31 to −0.13‰). Both δ 202 HgTGM and Δ 199 HgTGM showed clear seasonal variations, but the seasonal pattern of δ 202 HgTGM was different from that of Δ 199 HgTGM . The lowest mean δ 202 HgTGM was observed in spring (−0.15‰), while the lowest mean Δ 199 HgTGM was observed in summer (−0.24‰). A significant positive correlation (R 2  = 0.38, p  < 0.01) existed between δ 202 HgTGM and normalized difference vegetation index (NDVI), suggesting vegetation activity was an important factor controlling the seasonal variation of δ 202 HgTGM . In contrast, air mass transport path, which influences the source region of TGM to LABS, was likely the driver for the seasonal variations of Δ 199 HgTGM . Furthermore, results from the air mass classification showed distinguishable Δ 199 HgTGM signature for different air mass source regions, with air masses from South China Sea and western Pacific Ocean being characterized by more negative Δ 199 HgTGM (−0.25 ± 0.04‰). Results of this research demonstrated a clear difference in isotopic compositions of atmospheric Hg between continental and marine air masses. Graphical abstract: Image 1 Highlights: The first TGM isotope data reported from a mountain site downwind of East Asia. Isotopic signature of TGM with air from open oceans had significant negative Δ 199 Hg. Variability of δ 202 HgTGM was attributed to vegetation activity. Variation of Δ 199 HgTGM was driven by air mass transport paths.